A Study of Masson's Slope in Dioxane-Formamide Mixture by Magnetic Float Densitometer Using Tetra Alkyl Ammonium Iodides at 25 ºC - Maurya, Archana; Pathak, R.N. (Asian Journal of Chemistry, 2012)
Apparent molar volume of Et4NI, Pr4NI, Bu4NI and Pen4NI salt solutions have been determined in different compositions of dioxane-formamide mixture of (0, 15, 25, 35, 45 and 59 % formamide in dioxane) by density measurement at 25 ºC from apparent molar volume. The slope of Masson's equation have been analyzed for these salts. The obtained parameters have been interpreted in terms of polar and non-polar behaviour and hydrogen bonding of organic solvents used in the solutions. The slopes are found to be positive for all the electrolytes in different compositions of solvent mixtures except for 59 % formamide mixture in which all the R4NI salts gave negative slope.